1997
DOI: 10.1128/aem.63.5.1852-1860.1997
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Genotypic Fingerprinting of Fluorescent Pseudomonads Associated with the Douglas Fir-Laccaria bicolor Mycorrhizosphere

Abstract: A collection of 300 isolates of fluorescent pseudomonads was established from Douglas fir-Laccaria bicolor mycorrhizas and mycorrhizosphere and from adjacent bulk soil. These isolates were first phenotypically characterized with the Biolog method. Taxonomic identification assigned 90% of the isolates to the different biovars of Pseudomonas fluorescens, with inverted frequencies of biovars V and I from the bulk soil to the mycorrhizas, suggesting that the mycorrhizas exert a selective stimulation of the P. fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 43 publications
12
63
2
Order By: Relevance
“…This result suggests that the MHB are not strictly rhizobacteria. This hypothesis is in accordance with that of Frey-Klett et al [24] who demonstrated that helper bacteria (BBc6) of the mycorrhizal symbiosis between Laccaria bicolor and Douglas ¢r is associated with the mycelium of the fungus in the soil. Moreover, Sen et al [29] have demonstrated that BBc6 was attached to the hyphal wall of L. bicolor in in vitro experiments.…”
Section: Origin Of the Bacterial Isolatessupporting
confidence: 92%
See 1 more Smart Citation
“…This result suggests that the MHB are not strictly rhizobacteria. This hypothesis is in accordance with that of Frey-Klett et al [24] who demonstrated that helper bacteria (BBc6) of the mycorrhizal symbiosis between Laccaria bicolor and Douglas ¢r is associated with the mycelium of the fungus in the soil. Moreover, Sen et al [29] have demonstrated that BBc6 was attached to the hyphal wall of L. bicolor in in vitro experiments.…”
Section: Origin Of the Bacterial Isolatessupporting
confidence: 92%
“…These results reveal discrepancy with other results obtained with several mycorrhizal plant species such as Douglas ¢r [24], hybrid larch, Sitka spruce [25] and hazel trees mycorrhized with tru¥es [26]. However, in the present study, the soil was sampled just under some Pisolithus fructi¢cations where the yellow mycelial stands of Pisolithus sp.…”
Section: Origin Of the Bacterial Isolatescontrasting
confidence: 76%
“…Selection of specific bacterial communities by the ectomycorrhizosphere (Frey et al, 1997;Uroz et al, 2007;Izumi and Finlay, 2010) and the mycosphere (i.e. the hyphal network underneath fungal fruiting bodies; Boersma et al, 2009) has been reported for many ectomycorrhizal fungi.…”
Section: Discussionmentioning
confidence: 99%
“…However, they failed to ¢nd any relation between ARDRA identi¢cation and biochemical traits (Biolog pro¢les). In contrast, Frey et al [17] evidenced a strict correlation between the ARDRA classi-¢cation and the multivariate analysis of bacterial metabolic ¢ngerprinting for £uorescent pseudomonads isolated from the mycorhizosphere. They also found a close correlation between rep-PCR and metabolic ¢ngerprints.…”
Section: Discussionmentioning
confidence: 87%
“…This may account for di¡erences observed in rhizobacteria diversity between plant species and between genotypes of the same species [16]. The amount and composition of root exudates are in£uenced by environmental conditions [17,18], and are also under close genetic control [19]. 0168 Arabidopsis thaliana (L.), a small £owering plant of the Brassicaceae family, has been chosen as a`model organism' for molecular genetics of £owering plants and for study of plant^microbe interactions.…”
Section: Introductionmentioning
confidence: 99%